Analisis Peramalan Penjualan Serbuk Vanila (Ground Vanilla) dan Ekstrak Vanila (Extract Vanilla) pada PT. Tripper Nature, Bali - ERIKA, IRENE MICHIKO; DEWI, RATNA KOMALA; USTRIYANA, I NYOMAN GEDE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2021)
Ground Vanilla and Extract Vanilla Sales Forecasting Analysis  on Tripper Nature Company, Bali Sales forecasting analysis should be done by businesses to increase and maintain a particular sales objective. Tripper Nature applies made to order system instead of using sales forecasting method to determine the sales target. The study aims to: (1) identify the product profiles of PT. Tripper Nature, (2) analyze sales data pattern for ground vanilla and extract vanilla (3) determine the best quantitative sales forecast method (4) and make an estimation sales forecast for ground vanilla and extract vanilla. This study uses both qualitative and quantitative research methods. Data are analyzed using trend analysis, simple moving average, single exponential smoothing, double exponential smoothing, double exponential smoothing, decomposition additive, decomposition multiplicative, and ARIMA (Auto Regressive Moving Average). Data analysis is concluded by looking at the minimum rate from MSE (Mean Square Error), which means the best quantitative method. Based on the result, the product profiles of PT. Tripper Nature could be classified into five products, namely whole dried vanilla, vanilla cuts, ground vanilla, extract vanilla, and vanilla paste. Vanilla powder and vanilla extract show a seasonal data pattern which means that agricultural raw materials are not available all year round. The best quantitative method for vanilla powder is the simple moving average method with an MSE of 14,832. 878. The best quantitative method for vanilla extract is the additive decomposition method with an MSE of 2,305,189. The forecast estimate for the 24 periods of vanilla powder was 176,049.6 pounds and for the vanilla extract was 42,928.34 gallons. It is hoped that PT. Tripper Nature would consider using the forecasting methods to increase sales in the future.